O imaginário social de alunos migrantes da rede pública municipal de Florianópolis - Pereira, Lucélia Moreira (2020)
The increasing arrival of migrants from other regions of Brazil to the city of Florianópolis reflects in schools and the migrants' lives directly, as observed in the English language classes taught by the researcher. We observed that the migratory process contributes to new experiences, new perspectives, and new relationships of affection, thus fostering the imagination of these students in this journey that is simultaneously sensitive and symbolic. This research as a case study in a school located in the north of the island of Florianópolis has as its general objective to identify the elements that form the social imaginary of migrant students from the poles of latent culture (desires) and patent culture (pressures) present in their narratives. The specific objectives aim to identify the role of the school in the process of cultural and social adaptation of students, to verify the articulations of memory, silences, and affections in the narratives of migrant students and, finally, to unveil the orders of the images presented in the narratives. Considering man, a symbolic being that is constituted not only from his experiences and dreams but also from socially and culturally established beliefs and desires, it is necessary to adopt for this research as a methodology the culturanalysis of groups proposed by Paula Carvalho (1990). Culturanalysis allows the researcher to understand the cultural constitution of organizations, individuals, and their groups. The theoretical contribution of this dissertation is anchored in studies of the imaginary of authors such as Durand (1993, 1998, 2012), Pitta (2005), Bachelard (1990, 1997, 2019), and Silva (2012, 2016). In this work, we bring Schroeder (2014) and Araújo (2004) to discuss Imaginary and Education. Theoretical developments on social memory and identity are based on Pollak (1989), Halbwachs (1990), Candau (2019), Seligmann-Silva (2003, 2005, 2008), and Hall (2003, 2006). Regarding the discussion of affections and postmodernity, we bring to light authors such as Maffesoli (2001a, 2001b, 2011, 2014), Bauman (2000), and Le Breton (2009). The results indicate that the symbolic constitution of the social imaginary of these students, which runs through the school and its demands, as well as the various family constitutions that are reconfigured in this process, follow what Gilbert Durand (2012) called the anthropological dialectic. By sharing schèmes and archetypes related to the drive for change and overcoming, particular symbols emerge from the students' narratives on each path that repackages a myth that accompanies people in their incessant search for a more prosperous place, where dreams and yearnings are redesigned.